Factors contribute to harvest non-standard oil palm fruit bunches among settlers / Hasrul Azahar Ahmad Jamri - Ahmad Jamri, Hasrul Azahar (Faculty of Plantation and Agrotechnology, 2015)
Fresh Fruit Bunch (FFB) is whereby the level of ripeness of the oil palm fruit bunch is essential to gain the quality of palm oil. The classification of the fruit bunches are being done at the mill by the worker by doing sampling. The FFB need to be sent to the mill within 24 hours after harvested to retain the quality of palm oil. But, only ripe fruit bunch is needed to get the best product. However, the non-standard fruit bunch still be processed but will charged to penalty. But what are the factors of settlers harvesting non-standard FFB, will be studied throughout this research. To study the factors, several phase of methods need to be run such as distributing questionnaires to the settlers, getting ready for data analysis, data analysis and gain the result. TI1e independent data need to be studied are factors of knowledge, health and safety of the settlers towards the efficiency of harvesting which why they harvest non-standard fruit bunches. From this SPSS, Descriptive statistic will be conducted to find the value of frequency, mean, standard deviation and variation of the data. The Pearson correlation also needs to be analyzed to see the relationship among the independent variable, which will show the strong relationship. The Multiple Regression Method in the SPSS will be conducted to see the relationship between independent variables and dependent variable.